An ERP study of effects of regularity and consistency in delayed naming and lexicality judgment in a logographic writing system - Yum, Yen Na; Law, Sam-Po; Su, I-Fan; Lau, Kai-Yan Dustin; Mo, Kwan Nok (Frontiers in Psychology, 2014)
Phonological access is an important component in theories and models of word reading. However, phonological regularity and consistency effects are not clearly separable in alphabetic writing systems. We investigated these effects in Chinese, where the two variables are operationally distinct. In this orthographic system, regularity is defined as the congruence between the pronunciation of a complex character (or phonogram), and that of its phonetic radical, while phonological consistency indexes the proportion of orthographic neighbors that share the same pronunciation as the phonogram. In the current investigation, regularity and consistency were contrasted in an event-related potential (ERP) study using a lexical decision task and a delayed naming task with native Chinese readers. ERP results showed that effects of regularity occurred early after stimulus onset and were long-lasting. Regular characters elicited larger N170, smaller P200, and larger N400 compared to irregular characters. In contrast, significant effects of consistency were only seen at the P200 and consistent characters showed a greater P200 than inconsistent characters. Thus, both the time course and the direction of the effects indicated that regularity and consistency operated under different mechanisms and were distinct constructs. Additionally, both of these phonological effects were only found in the delayed naming task and absent in lexical decision, suggesting that phonological access was non-obligatory for lexical decision. The study demonstrated cross-language variability in how phonological information was accessed from print and how task demands could influence this process.